Implementation of Character Education in Elementary School Using The QR Code During The Covid-19 Pandemic - Umar Diharja; Dwi Yanti; Rambat Nur Sasongko; Muhammad Kristiawan (Ta'dib: Jurnal Pendidikan Islam, 2022)
The application of character education during the Covid-19 pandemic underwent changes that needed to be adapted to conditions, one of which was character education in elementary schools. This study aimed to know the implementation of character education using the QR Code at SDIT Mutiara Cendekia Lubuklinggau. This study was conducted by implementing qualitative method. The data were collected through documentation and interviews with two teachers and the principal of the school while the data analysis was conducted through inductive techniques, through steps of data reduction, data display and drawing conclusion. The research findings showed the following results: 1) character education was still carried out despite the Covid-19 pandemic; 2) the use of QR code technology in the form of photos or videos made them attractive for the students Thus, the character education by using QR codes for character education at SDIT Mutiara Cendekia Lubuklinggau could run well regardless of the Covid-19 pandemic.